En grænse for transgressionen? - Mikkel Jensen (Akademisk Kvarter, 2011)
A similar interest in the normative, although in a different manner, is broached by Mikkel Jensen in his article En grænse for transgressionen? in which Jensen looks at different kinds of transgression; social or personal, finding that transgression becomes a way of self-development but also holds the risk of serving as an empty act.